How Public Works Authority Has Built a Portfolio Dashboard Through Agility Approach - Mchaweh, Abdulrahman (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The aim of this paper is to share PWA experience to develop a Portfolio Performance Dashboard (PPD) that suits its unique requirements. The case study sheds light on the challenges that PWA faced to develop an interim front reporting solution that deals with multiple scattered reporting systems within the different components of the portfolio. This paper demonstrates how PWA adopted Agility project management to develop a short-term dashboard solution for executive management.